Neonatal Mortality Rate and Its Causes at Maternity Wards in Baghdad City’s Hospitals - Amna Mahmood Khalf; Hala Saadi Abdul Wahid (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The first 28 days of life – the neonatal period – is the most vulnerable time for a child’ssurvival. Children face the highest risk of dying in their first month of life at an average global rate of (17)deaths per (1,000) live births in 2019.Objectives: To find out the neonatal mortality rate at maternity wards in Baghdad City’s Hospital for theyear 2019, and to assess the causes of neonatal mortality rate.Methods The study included a non-probability (convenient) sample of (150) Neonate who have beendyinginten hospitals in Baghdad City. The study subjects are recruited from 10 teaching hospitals. Data is collectedfrom neonatal medical records in the Department of Statistics; data are analyzed using descriptive andinferential data analysis process.The Results: The results of the current study indicate that the neonatal mortality ratefor the year of 2019 is(0.636).The highest number of causes of neonatal mortality is accounted for asphyxia (57.7%) and congenitalanomalies (29.6%).Most of the neonates are (1-5) day of age (83.8%); Males (64.1%); (3000-3.999) gm ofweight (42.9%); urban residents (60.6%); are born at early term (37 to 38+6 days) (35.9 %) and in hospital(95.8%) through cesarean section (64.8%). There is no significant relationship between neonates’ age andthe causes of neonatal mortality.Conclusion: The neonatal mortality rate is (0.636) for the year of 2019 on the maternity wards in BaghdadCity’s hospitals per 1000 of the population at risk for the same year; The most accounted cause of neonatemortality is asphyxia and congenital anomalies.